Hydrated Peridotite – Basaltic Melt Interaction Part I: Planetary Felsic Crust Formation at Shallow Depth - Borisova, Anastassia Y.; Zagrtdenov, Nail R.; Toplis, Michael J.; Bohrson, Wendy A.; Nédélec, Anne; Safonov, Oleg G.; Pokrovski, Gleb S.; Ceuleneer, Georges; Bindeman, Ilya N.; Melnik, Oleg E.; Jochum, Klaus Peter; Stoll, Brigitte; et al. (Frontiers in Earth Science, 2021)
Current theories suggest that the first continental crust on Earth, and possibly on other terrestrial planets, may have been produced early in their history by direct melting of hydrated peridotite. However, the conditions, mechanisms and necessary ingredients for this crustal formation remain elusive. To fill this gap, we conducted time-series experiments to investigate the reaction of serpentinite with variable proportions (from 0 to 87 wt%) of basaltic melt at temperatures of 1250 to 1300°C and pressures of 0.2 to 1.0 GPa (corresponding to lithostatic depths of ~5 to 30 km). The experiments at 0.2 GPa reveal the formation of forsterite-rich olivine (Fo90-94) and chromite coexisting with silica-rich liquids (up to 57 – 71 wt% SiO2). These melts share geochemical similarities with tonalite-trondhjemite-granodiorite rocks (TTG) identified in modern terrestrial oceanic mantle settings. By contrast, liquids formed at pressures of 1.0 GPa are poorer in silica (~50 wt% SiO2). Our results suggest a new mechanism for the formation of the embryonic continental crust via aqueous fluid-assisted partial melting of peridotite at relatively low pressures (~0.2 GPa). We hypothesize that such a mechanism of felsic crust formation may have been widespread on the early Earth and, possibly on Mars as well, before the onset of modern plate tectonics and just after solidification of the first ultramafic-mafic magma ocean and alteration of this primitive protocrust by seawater at depths of less than 10 km.